A inovação no desenvolvimento de produtos do fast-fashion - Cimenton, Laís Queiroz [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This paper aims to verify how it is possible to add value to the fast-fashion brands, trought the innovation on product development. So, it is defined the context that the organizations are in, which are the expectations of the consumers and which are the possible strategies that can be used to innovate and create competitive advantage. This paper presents a literature review and a field research, and can be found on it some concepts of authors like Kotler, Kartajaya e Setiawan (2010), Treptow (2013), Cobra (2010), Kalil (2010), Bes e Kotler (2011), Jugend e Silva (2013), Costa (2013), Cietta (2010), and others. As a way of creating value to the brand, a proposal of co-creation implementation on product development process is made, with the aim of creating a network interaction and sharing between the organization and consumers.

O objetivo desde trabalho foi verificar como é possível agregar valor às marcas do fast-fashion por meio da inovação no desenvolvimento de produtos. Para tanto, foram definidos o contexto em que as organizações estão inseridas, as expectativas dos consumidores e as possíveis estratégias a serem traçadas a fim de inovar e criar vantagem competitiva. Este trabalho apresenta uma revisão bibliográfica e pesquisa de campo, e são encontrados conceitos de autores como Kotler, Kartajaya e Setiawan (2010), Treptow (2013), Cobra (2010), Kalil (2010), Bes e Kotler (2011), Jugend e Silva (2013), Costa (2013), Cietta (2010), entre outros. Como forma de criar valor à marca, foi proposta a implementação da cocriação no processo de desenvolvimento de produtos, a fim de criar uma rede de interação e compartilhamento entre organização e consumidores.
Keywords: Marketing; Comercio varejista; Moda; Fashion